MARTYRDOM OF PROPHET'S UNCLE IN THE MESSAGE MOVIE DIRECTED BY MOUSTAPHA AKKAD (1976): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - OKTAVIANINGRUM, IKA DEWI (2011)
This research paper elaborates the motives underlying martyrdom of Hamza in The Message which are analyzed through an individual psychological approach. The objective of the research is to analyze the movie based on its structural elements and based on an individual psychological approach. This research belongs to qualitative research. The type and the data source which are used, namely primary and secondary data. The primary data source is the movie itself. The secondary data sources are taken from books and other sources which support the analysis. The method of the data collection is library research and the technique of the data analysis is descriptive technique. Having analyzed the movie, first, the writer summaries that the structural elements of the movie are united to each other. Second, the writer draws that the major character of the movie can be said as self-actualized person because the characteristics of self-actualization have been portrayed in his personality.